Pertumbuhan Kedelai melalui Aplikasi Asam Askorbat dan Inokulasi Fungi Mikoriza Arbuskular pada Lahan Salin dengan Tingkat Salinitas yang Berbeda - Romi Martino Sitanggang; Nini Rahmawati; Chairani Hanum (Jurnal Agroekoteknologi, 2014)
Utilization of saline soil for soybean cultivation will decrease soybean production. Micorizainoculation and ascorbate acid treatment on saline soil will give a positive response to the soybeangrowth and production. This research was conducted at experimental field Kecamatan Percut SeiTuan Kabupaten Deli Serdang during Februari – Mei 2013, using split split plot design with threefactors. The main factor was salinity level were electrical conductivity 4-5 mmhos/cm and II:electrical conductivity 6-7 mmhos/cm. The sub plot was giving of ascorbate acid (0 dan 500 ppm)and MVA inoculants (MVA inoculants type 1, type 2, type 3, type 4 and type 5) as sub sub plot.The result of the research showed that single factor micorhizae innoculation or ascorbate acidapplication showed gave a positive response of root infection degree, root dry weight, root volume,shoot dry weight, number of pods per plant contains, the number of empty pods per plant and 100seed weight. Aplication mycorrhizal and ascorbic acid on Saline soils with dhl 4-5 will increasesoybean growth, production, and highest degree of root infection.